1997
DOI: 10.1074/jbc.272.33.20564
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric G Proteins Control Exocytosis in Chromaffin Cells

Abstract: Besides having a role in signal transduction, heterotrimeric G proteins may be involved in membrane trafficking events. In chromaffin cells, G o is associated with secretory organelles and its activation by mastoparan inhibits the ATP-dependent priming of exocytosis. The effectors by which G o controls exocytosis are currently unknown. The subplasmalemmal actin network is one candidate, since it modulates secretion by controlling the movement of secretory granules to the plasma membrane. In streptolysin-O-perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 66 publications
2
30
0
2
Order By: Relevance
“…These vesicles are not identical to Glut4-containing vesicles that are also sensitive to insulin and not identical to endosomes that often involve in the exocytotic pathways. It appears that these vesicles are similar to hormone-containing secretory vesicles in endocrine cells such as chromaffin cells (Gasman et al 1997, Steyer et al 1997) and chromaffin-derived PC12 cells (Zhang et al 2008) in terms of size and characteristics in trafficking. In addition, reagents that stimulate (or inhibit) the secretion of these adipokines also facilitate (or reduce) its vesicle trafficking.…”
Section: Discussionmentioning
confidence: 98%
“…These vesicles are not identical to Glut4-containing vesicles that are also sensitive to insulin and not identical to endosomes that often involve in the exocytotic pathways. It appears that these vesicles are similar to hormone-containing secretory vesicles in endocrine cells such as chromaffin cells (Gasman et al 1997, Steyer et al 1997) and chromaffin-derived PC12 cells (Zhang et al 2008) in terms of size and characteristics in trafficking. In addition, reagents that stimulate (or inhibit) the secretion of these adipokines also facilitate (or reduce) its vesicle trafficking.…”
Section: Discussionmentioning
confidence: 98%
“…We recently identified another putative effector of G o in the exocytotic pathway, namely the 2 M.-C. Galas and M.-F. Bader, unpublished data. monomeric GTP-binding protein Rho, which seems to regulate the peripheral actin network (41). Interestingly, several reports describe a reciprocal regulatory relationship between actin reorganization and PLD activity (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the secretory granule-associated G o protein regulates the peripheral cytoskeleton in chromaffin cells by a mechanism involving the small GTP-binding protein Rho (20). Since phosphoinositide kinases are potential effectors for Rho in mediating cytoskeletal rearrangements (21-23), we investigated the possible functional relationship between the granulebound form of G o , RhoA, and the PtdIns 4-kinase activity described in chromaffin granule membranes (28,29).…”
Section: Effect Of Mastoparan and Gap-43 On The Secretory Granuleassomentioning
confidence: 99%
“…Rho together with a trimeric G protein regulates the changes in the actin cytoskeleton observed in activated mast cells (17,27). In chromaffin cells, we recently described that the secretory granule-associated G o controls the priming of exocytosis by modifying the cortical actin network through a sequence of events that eventually involves Rho (20). Thus, Rho seems to be an integral component of the signaling pathway leading to the cytoskeletal redistribution necessary for secretion, although the mechanism by which Rho relates to the actin organization remains to be elucidated.…”
mentioning
confidence: 99%